In-Situ Hollow Sample Setup Design for Mechanical Characterisation of Gaseous Hydrogen Embrittlement of Pipeline Steels and Welds - Tim Boot; Ton (A. C.) Riemslag; Elise (T. E.) Reinton; Ping Liu; Carey L. Walters; Vera Popovich (Metals, 2021)
This work discusses the design and demonstration of an in-situ test setup for testing pipeline steels in a high pressure gaseous hydrogen (H2) environment. A miniature hollow pipe-like tensile specimen was designed that acts as the gas containment volume during the test. Specific areas of the specimen can be forced to fracture by selective notching, as performed on the weldment. The volume of H2 used was minimised so the test can be performed safely without the need of specialised equipment. The setup is shown to be capable of characterising Hydrogen Embrittlement (HE) in steels through testing an X60 pipeline steel and its weldment. The percentage elongation (%El) of the base metal was found to be reduced by 40% when tested in 100 barg H2. Reduction of cross-sectional area (%RA) was found to decrease by 28% and 11% in the base metal and weld metal, respectively, when tested in 100 barg H2. Benchmark test were performed at 100 barg N2 pressure. SEM fractography further indicated a shift from normal ductile fracture mechanisms to a brittle transgranular (TG) quasi-cleavage (QC) type fracture that is characteristic of HE.